A template for the audio introduction of operas: A proposal - Iturregui Gallardo, Gonzalo; Permuy Hércules de Solás, Iris Cristina (Hikma, 2019)
Audio Introductions (AI) consist of a brief description of the plot, history and technical aspects of an audiovisual product and are generally presented at the beginning of an operatic event. Despite their prevalence, literature related to the elaboration of AI in audio description (AD) guidelines is scarce. Continuing the investigation carried out by the research group Transmedia Catalonia in the field of AD for opera, this article focuses on the role of AI in opera, not only as an access service for the blind and visually impaired audience, but also for all audience members. Furthermore, a template for AIs is put forward, in which the contents that AIs should cover for the appropriate presentation of the information relevant to the opera are detailed and explained. The article delves into these contents and underscores their importance for enhancing the experience of the opera for both the visually impaired and the general audience. The creation and distribution of a template draws attention to the potential of standardisation of this access service. The article is based on the analysis of a template used at the Gran Teatre del Liceu of Barcelona by the audio describer, also a co-author of the article, employed in the production of AIs throughout the opera season 2016/17. The creation of AIs by means of the template improved the work flow by providing a clear understanding of the topics to be covered beforehand and by outlining the time constraints during the live performance on the contents.